Anoles & Drones: revealing controls on anole abundance and mapping sub-canopy thermal habitat using remote sensing, on the island of Utila, Honduras - Higgins, Emma A. (2022)
In these times of rapid environmental change and species extinction, understanding the drivers and mechanisms governing species’ abundance is more important than ever. The goal of this thesis was to further our understanding of what drives variation in species’ abundance and microhabitat use through space, particularly in the context of rapid land cover and climate change, using the little explored anole fauna of the Honduran island of Utila. The work uncovered that when considering structural habitat, prey availability and the thermal environment, for the endemic Anolis bicaorum, thermal habitat quality and prey biomass both had positive direct effects on anole abundance. However, thermal habitat quality also influenced prey biomass, leading to a strong indirect effect on abundance. Consequently, the later part of this thesis focuses on the thermal environment and the use of unoccupied aerial vehicles (UAVs) and satellite remote sensing platforms for mapping thermal habitat quality and availability at scales relevant to the species. Thermal habitat quality for A. bicaorum was primarily a function of canopy density, measured as leaf area index (LAI), therefore this work combined indices of canopy cover and heterogeneity derived from UAV and WorldView-2 satellite imagery to map sub canopy operative temperature (Te). Results indicate that such methods as using remote sensing imagery, when coupled with air temperature measures, are a reasonable way of mapping Te continuously across space, allowing us to quantify the availability and spatial structure of the thermal environment, at spatial scales experienced by the organism. Lastly, I used WorldView-2 imagery and the proposed methods for mapping Te to quantify available thermal habitat for A. bicaorum on Utila across land cover and climate scenarios. This work indicates the need to determine controls and niche interactions on animal abundance and the importance quantifying these niche factors at relevant spatial scales to estimate species responses to land cover and climatic change.